“Ecologically camping, eating, drinking wine.” Material and knowledge flows in the Minimum Cost Housing Group’s ECOL Operation, 1971-76 - Lee Stickells (ABE Journal)
For approximately fifty years, McGill University’s Minimum Cost Housing Group (MCHG) has undertaken research on the “human settlement problems of the poor.” This paper focuses on the group’s activities from 1970 to1976, and more specifically the “ECOL Operation” initiated by the group’s first director, Colombian architect and UN consultant Alvaro Ortega. The story of the ECOL Operation gives insight into some unanticipated feedback loops associated with the foreign-aid-funded knowledge economy. The ECOL Operation was pitched as a technical and material research program to develop self-help housing solutions for the “Third World.” In practice, it was an improvised mix of international development aspiration, Appropriate Technology enthusiasm, industrial research and development, and ecological design rhetoric. The paper argues that the MCHG’s efforts became most compelling as a blueprint for a set of designers and activists rethinking the consumerist lifestyles and material flows of the Global North. This highlights a more complex background to the counterculturally-inflected ventures of 1970s ecological design. The scene was more closely connected to the Cold War complex of intergovernmental organizations, development agendas, and industrial capitalism than its participants may have imagined.